2012
DOI: 10.12659/msm.882727
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin accelerates the healing of cysteamine-induced duodenal ulcers in rats

Abstract: SummaryBackgroundPrevious studies have shown that administration of ghrelin exhibits protective and therapeutic effects in the gut. The aim of the present investigation was to examine the influence of ghrelin administration on the course of cysteamine-induced duodenal ulcers, as well as effects on mucosal production of oxygen free radicals and duodenal antioxidant defense.Material/MethodsDuodenal ulcers were induced in male Wistar rats by cysteamine administered intragastrically at the dose of 200 mg/kg in 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 51 publications
2
25
0
2
Order By: Relevance
“…demonstrated that ghrelin prevents lipid peroxida tion and decrease of antioxidant enzyme activities against pentylenetetrazole induced oxidative stress in erythrocyte s, liver and brain in rats . Moreover, several studies showed that, ghrelin significantly increases the activity of antioxidant enzymes such as GP x , SOD and CAT and decreases the concentr ation of malondialdehyd e, a product of lipid peroxidation (Kheradm and et al, 2009;Warzecha et al, 2012 ). In consistency with the literature, we also determined the antioxidant property of ghrelin via TAS and TOS levels.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…demonstrated that ghrelin prevents lipid peroxida tion and decrease of antioxidant enzyme activities against pentylenetetrazole induced oxidative stress in erythrocyte s, liver and brain in rats . Moreover, several studies showed that, ghrelin significantly increases the activity of antioxidant enzymes such as GP x , SOD and CAT and decreases the concentr ation of malondialdehyd e, a product of lipid peroxidation (Kheradm and et al, 2009;Warzecha et al, 2012 ). In consistency with the literature, we also determined the antioxidant property of ghrelin via TAS and TOS levels.…”
Section: Discussionsupporting
confidence: 75%
“…Ghrelin has been proposed as an antioxidant agent recently in several studies (Kheradm and et al, 2009;Warzecha et al, 2012 ). Obay at al.…”
Section: Discussionmentioning
confidence: 99%
“…The area of colonic mucosa damage was measured using the computerized planimeter (Morphomat, Carl Zeiss, Berlin, Germany), as described previously [27,69]. …”
Section: Methodsmentioning
confidence: 99%
“…In animal models, ghrelin administration has promoted acceleration on the healing of gastric and duodenal ulcers by releasing endogenous GH and IGF-1 and leading an increasing of mucosa blood flow and local cell proliferation rate 57 . Warzecha et al 58 also have demonstrated an improvement of healing process in cisteamine-induced duodenal ulcers assessing reduction of mucosal OS and inflammatory response and reduction of mucosal OS and inflammatory response Ercan et al 59 have reported decrease of apoptosis and OS in sodium metabisulfite induced gastric injury, suggesting that ghrelin treatment attenuates gastric injuries and could improve approaches against gastric mucosal injury.…”
Section: Effects Of Ghrelin In the Gutmentioning
confidence: 98%